IMPROVING STUDENTS COMPETENCE IN WRITING SPOOF TEXT THROUGH GROUP DISCUSSION : A CASE OF THE ELEVENTH GRADE STUDENTS OF SMAN 01 GRINGSING - Eka Puspawati (ETERNAL (English Teaching Journal), 2014)
Group Discussion is a modern method of assessing students personality. The objectives of the study are (1) to find out the students’ writing ability through group discussion and without group discussion, (2) to know if there is any significant difference of the students’ writing ability between using group discussion and without group discussion technique. The type of this research was experimental research. The sample were selected two classes by using cluster random sampling. Each class consisted of 30 students as experimental group and control group. Data were collected by using test and treatment. The instrument of this research was written test. The mean of post-test in control group is 71.83 and the mean of post-test in experiment group is 74.00. Then the t-test score obtained is 5.565 with degree of freedom (df) is 58. From the result of significant t- value is higher than t-table (5.565 > 1.671), it can be concluded that Ho (negative hyphothesis) is rejected. It means that Ha (positive hyphothesis) can be accepted. The conclusion is that using group discussion to teach writing spoof text for the students has significant effect for the improvement of students’ ability in writing spoof text.